Distributed Predictive Control Using Frequency and Voltage Soft Constraints in Ac Microgrids Including Economic Dispatch of Generation - Espina-Gonzalez, E (IEEE Computer Society, 2021)
This paper proposes a distributed predictive secondary controller to tackle together frequency and voltage regulation, realize the economic dispatch and reactive power sharing of generation units in isolated AC microgrids. Contrary to most approaches, the proposed predictive controller achieves consensus objectives (economic dispatch of generation and reactive power sharing) with soft constraints (keep both frequency and average voltage within predefined bands instead of restoring them to their nominal values). Extensive simulation work validates the effectiveness of the predictive controller for communication problems and in the presence of plug-and-play scenarios. © 2021 IEEE.